Rethinking Condition: Measuring and Evaluating Wetland Vegetation Responses to Water Management - Campbell, Cherie J.; Thompson, Ross M.; Capon, Samantha J.; Dyer, Fiona J. (Frontiers in Environmental Science, 2022)
Environmental water management is increasingly used to restore riverine, wetland and floodplain ecosystems and requires an understanding of what the flow regime or restoration objectives are, why these objectives are being targeted and how outcomes will be evaluated. This perspective paper focuses on non-woody vegetation, an important component of river-floodplain ecosystems and a targeted outcome for many environmental flow management programs, such as the Basin wide environmental watering strategy for the Murray-Darling Basin in Australia. Effective management of non-woody vegetation using environmental water requires identifying a suite of measurable condition outcomes (the ‘what’), understanding how these relate to broader functions and values (the ‘why’) and developing clear cause-and-effect relationships between management and outcomes (the ‘how’). A critical component of this process is to characterise what constitutes management success, which requires reimagining current definitions of condition to better incorporate dynamic functions and diverse values. We identify the need to characterise condition in a structured framework using both ecological data and societal values. This approach will not only help inform the development of benchmarks, watering objectives and monitoring metrics, but will also facilitate engagement by a broader spectrum of the community with the management and outcomes of environmental watering.